International Conference on Transportation and Development 2022. selected papers from the International Conference on Transportation and Development 2022, Seattle, Washington, May 31-June 3, 2022 - Wei, Heng (Civil engineer) (American Society of Civil Engineers, 2022)
This collection contains 24 peer-reviewed papers on emerging transportation technologies presented at the International Conference on Transportation and Development 2022, held in Seattle, Washington, May 31-June 3, 2022. Topics include: AI and machine learning; traffic patterns and modeling; deep learning; and vehicle tracking.